Il paradosso del mentitore - Alessandro Di Caro (Linguae &: Rivista di Lingue e Culture Moderne, 2021)
The liar paradox is an ancient logical paradox (revisited by modern thinkers) which links truth with falsehood and falsehood with truth, and is based on a self-referential mechanism. It has been discussed by a variety of authors, from Aristotle to Bateson. The solution to that paradox, however, can be found by having recourse to Ludwig Wittgenstein’s philosophy, and by, so to speak, getting out of language (because true and false are words which belong to our language) to attain reality. This can be expressed through Wittgenstein’s idea that no proposition can say of itself whether it is true or false. However, experience is also expressible in words – and one can think of propositions which cannot be confirmed or disproved according to experience. Studying the paradox, therefore, leads one to Gödel’s theorem which offers a mathematical demonstration of the existence of undecidable propositions.